A Case Control Study to Determine the Effectiveness of Mean Platelet Volume (MPV) in Acute Appendicitis Diagnosis among Children - Saifullah Brohi, Sajid Anwer, Faran Hamid, Yasir Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To access the diagnostic value of the mean platelet volume in children with acute appendicitis. Study design: A case control study Place and duration: In the Surgical department of Bilawal Medical College for Boys LUMHS, Jamshoro and Sheikh Zayed Medical College/ Hospital Rahim Yar Khan for six-months duration from July 2021 to December 2021. Methods: 150 total patients were selected with the WHO formula with SD 1.09, 80% power, 5% significance level with cases to control ratio of 1:1 and expected populace 7.55. The patients were selected with simple random technique of sampling (lottery method). The continuous variables of both groups were compared by means of the t-test. To determine the association of MPV with other variables; correlation test was applied. Results: The study included 150 patients; 35 (46.7%) are men and 40 (53.3%) are women in the study group and 34 (45.3%) men and 41 (54.7%) women in the control group. 8.21 ± 3.51 (1-15 years) was the mean age of the patients in the study group and the mean age of the controls was 8.69 ± 3.51 (1-15 years). The specificity for raised neutrophil and WBC values ​​was 91% and 89%, and the sensitivity was 77% and 84%, respectively. The sensitivity and specificity to MPV reduction was 87% and 54%. Conclusion: The increase in the leukocytes and neutrophils is significantly associated with acute appendicitis diagnosis. It is less costly and less time-consuming which cause more attention to MPV values ​​during complete blood counts in the acute appendicitis diagnosis among pediatric patients. The low MPV levels are encountered in children with acute appendicitis. Keywords: High white blood cell count, acute appendicitis, specificity, mean platelet volume (MPV).